The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/dcr.0b013e3181a7476a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Use of Posterior Tibial Nerve Stimulation for the Treatment of Fecal Incontinence: Preliminary Results of a Prospective Study

Abstract: Percutaneous tibial nerve stimulation is a minimally invasive and effective treatment option for patients with fecal incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 16 publications
5
55
2
1
Order By: Relevance
“…Furthermore, improvements in patient quality of life have been observed. 22,24,25,26,27 Consistently, PTNS also improved the FI score and quality-of-life values in our study. In addition, 15 (68%) patients experienced more than 50% reduction in the number of FI episodes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, improvements in patient quality of life have been observed. 22,24,25,26,27 Consistently, PTNS also improved the FI score and quality-of-life values in our study. In addition, 15 (68%) patients experienced more than 50% reduction in the number of FI episodes.…”
Section: Discussionsupporting
confidence: 87%
“…The session duration is usually 30 minutes, and the session frequency varies between once or twice per week and every other day, with the total treatment duration ranging from 6 weeks to 3 months. 22,24,25,26 We used a protocol of 30-minute sessions per week and a total of 10 sessions because a substantial portion of patients lived far from the clinic. Previous studies of PTNS have revealed that the procedure reduces the frequency of FI episodes by more than 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Direct comparison with other studies is difficult because of aetiologic heterogeneity, the different protocols of PTNS administration and the various methods used to quantify any improvements. Nevertheless, our results provide further evidence that PTNS may be a simple, safe and effective treatment for FI [4][5][6].…”
Section: Discussionmentioning
confidence: 55%
“…Increasing evidence suggests that percutaneous tibial nerve stimulation (PTNS) is an effective treatment for FI with demonstrable improvement in clinical outcomes and quality of life scores [2,[4][5][6][7]. The published literature, however, is limited to a few methodologically heterogeneous studies with small numbers of participants.…”
Section: Introductionmentioning
confidence: 97%
“…Otra modalidad de neuromodulación es la periférica, que consiste en la electroestimulación del nervio tibial posterior con electrodos percutáneos, lo que ha mostrado efectividad en la mejoría de la incontinencia, faltando estudios con mayor cantidad de pacientes que confi rmen esos resultados 40 .…”
Section: Neuromodulación Sacraunclassified